Faktor-faktor yang mempengaruhi kinerja keuangan pada bank umum syariah di Indonesia - Suratminingsih Suratminingsih; Patriandari Patriandari; Sari Mujiani; Nur Rizkiyana (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to determine the effect of mudharabah, musyarakah, murabahah, and ijarah financing on banking performance. The population in this study includes Islamic commercial banks for the 2015-2020 period. The sample in this study was taken using the purposive sampling method with certain criteria. Based on the predetermined criteria, the sample used is 8 samples with a total of 48 data. The analytical method used is Descriptive Statistics, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Test, and Hypothesis Testing using an analytical tool in the form of SPSS (Statistics Product and Service Solutions). The results of this study indicate that: mudharabah financing has a positive effect on banking performance, musyarakah financing has a negative effect on banking performance, murabahah financing has a negative effect on banking performance, ijarah financing has a positive effect on banking performance.